FOOD ESTATE DAN GOVERNMENTALITY: KEKUASAAN NEGARA DALAM MEMBENTUK SUBJEKTIVITAS PETANI - Vellayati Hajad; Safril Yanda; Ikhsan Ikhsan; Herizal Herizal (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This article examines the Food Estate project in Indonesia by addressing how state food policy functions as a technical intervention and a power mechanism shaping how farmers think and act. The study aims to understand how the state produces and normalizes specific forms of knowledge through policy mechanisms and development discourse. The author argues that Food Estate operates as a project of governmentality, constructing farmer subjectivity aligned with state logic while simultaneously establishing a regime of truth that marginalizes local agrarian practices. Using critical discourse analysis within Michel Foucault’s theoretical framework particularly the concepts of genealogy, governmentality, and the regime of truth this research traces how narratives of crisis, modernization, and efficiency are legitimized through technocratic apparatuses and networks of power. The findings reveal that state power operates through instruments such as data, technology, subsidies, and regulation, subtly disciplining farmers to conform to national production standards. However, various forms of micro-resistance and counter-narratives have emerged from local communities, challenging the project’s legitimacy. The study concludes that the Food Estate is a non-neutral apparatus of power that must be structurally critiqued. The authors recommend recognizing the plurality of local knowledge, strengthening substantive community participation, and opening political and epistemic space for alternative narratives as part of agrarian democratization and sustainable food sovereignty.